(untitled) (The Pretoria Student Law Review, 2021)
This article falls upon the backdrop of a highly debated and controversial area of the law. In 2009 a homosexual minister was dismissed from her position at a Methodist church upon announcement of her impending marriage to her female partner.1 This opened up the pertinent question of whether such a person constitutes an employee for purposes of labour law, which is what this article seeks to address.